Potential health effects of cyanide use in artisanal and small-scale gold mining in Burkina Faso. (10th April 2020) - Knoblauch, Astrid M.; Farnham, Andrea; Ouoba, Joël; Zanetti, Jessica; Müller, Stefanie; Jean-Richard, Vreni; Utzinger, Jürg; Wehrli, Bernhard; Brugger, Fritz; Diagbouga, Serge; Winkler, Mirko S.
Abstract: The artisanal and small-scale gold mining (ASGM) sector in Burkina Faso increasingly employs cyanide leaching to exploit the natural resource gold. The long-term consequences of chronic cyanide exposure in humans have yet to be fully elucidated. Meanwhile, the local health and development actors are facing immediate, unfamiliar challenges. The aim of this study was to deepen the understanding of cyanide exposure pathways, potential human exposure and associated health effects in ASGM communities in order to tailor health promotion and sustainable development recommendations for local actors. In April and May 2017, a cross-sectional epidemiological study was carried out in three ASGM sites in Burkina Faso. Three exposure groups were included: (i) miners using cyanide; (ii) miners who do not use cyanide; and (iii) ASGM community members not directly involved in mining. A questionnaire was administered to all study participants, followed by a finger prick blood sample to determine blood lactate level as a proxy indicator for cyanide exposure. Overall, 279 individuals participated (99 cyanide-using miners, 90 non-cyanide using miners and 90 community members not involved in mining activities). Mean blood lactate levels were significantly higher in miners using cyanide (4.7 mmol/L, 95% confidence interval (CI) 3.8–5.6 mmol/L), compared to non-cyanide using miners (3.4 mmol/L, 95% CI 2.9–3.7 mmol/L) and other community members not involved in mining activities (2.8 mmol/L, 95% CI 2.4–3.2 mmol/L). Multiple linear regression found loss of short-term memory reported by participants associated with higher blood lactate level. In view of our findings, we conclude that the use of cyanide in Burkina Faso's ASGM sector is associated with potential negative health effects. Hence, specific public health interventions are warranted, such as raising awareness among miners of the risks of cyanide use, promotion of protective measures and strengthening of health sector capacities to recognize and manage mining-related health issues and law enforcement. Highlights: Our study in Burkina Faso identified factors associated with higher blood lactate levels. Blood lactate levels in community members not mining were above normal values. Cyanide exposure poses an immediate local health challenge.